Can Creative Canva For Creative Branding (Logo Design & Product Packaging Assistance) In Mojokampung Village, Bojonegoro District, Bojonegoro Regency and Montong Village, Tuban District, Tuban Regency - Cipnal Muchlip; Nurul Jariyatin; Adib Nurdiyanto; Fathur Rochman (LPPM ISTeK ICsada Bojonegoro, 2026)
This Community Service activity through the CAN CREATIVE CANVA FOR CREATIVE BRANDING program aims to empower Micro, Small, and Medium Enterprises (MSMEs) by improving their skills in logo and product packaging design as an effort to strengthen business branding. The program was implemented in Mojokampung Village, Bojonegoro District, Bojonegoro Regency and Montong Village, Tuban District, Tuban Regency. The implementation methods included counseling on the importance of product branding, training on the use of Canva as an accessible graphic design application, and direct assistance in the process of designing logos and product packaging. The results indicate an increase in participants’ understanding and skills in creating more attractive, communicative, and marketable product visual identities. This activity is expected to enhance the competitiveness of local products and support the development of a community-based creative economy.